Predicting brain age from EEG signals using machine learning and neural network - Pratanu, Abul Mushfique Muslah; Farhad, Fuad Ibne Jashim; Afnan, Aysha; Mim, Nusrat Jahan; Rahman, Farhin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.